PENGARUH MOTIVASI BELAJAR TERHADAP KETERAMPILAN MENYIMAK SISWA KELAS V SD NEGERI NO, 59 PANYANGKALANG KABUPATEN TAKALAR - Hamdani; Ummu Khalsum; Sri Rahayu (Nusantara Hasana Journal, 2022)
The main problem in this study is whether there is an effect of verbal motivation on students' listening skills, this study aims to. The Influence of Motivation on Listening Skills for Fifth Grade Students at State Elementary School No, 59 Panyangkalang, Takalar Regency. The type of research used by the researcher is experimental, using a pre-experimental research design with the type of one group pretest posttest. Data were collected using a questionnaire and also a test. The results of the normality test showed that the pretest significant value > 0.05 or 0.000 > 0.05 and the posttest significant value > 0.05 or 0.174 > 0.05. Where the significant value is greater than 0.05, the research data is declared to be normally distributed. The homogeneity test using showed that the significant value was > or 0.014 > 0.05. The data is declared homogeneous, the value is significantly greater than the standard level (α ). Hypothesis testing shows the value of tcount > ttable or 5.834 > 2.22814. If tcount is greater than t table, then H0 is rejected and H1 is accepted so that it can be concluded that Learning Motivation Treatment has an influence on the Listening Skills of fifth grade students at SD Negeri No. 59 Panyangkalang, Takalar Regency. The results of listening skills before being taught using the Motivation Treatment level of mastery in the medium and high categories, after using the Learning Motivation Treatment reached the high and very high categories. So it can be concluded that Learning Motivation Treatment can be used to improve students' listening skills.